«Allí está España»: el imaginario nacional en El Instructor, o repertorio de historia, bellas letras y artes (1834-1841) - David Loyola López (Cuadernos de Ilustración y Romanticismo)
El Instructor, o repertorio de historia, bellas letras y artes was the most long-standing and extensive publication in Spanish language published in England during the first half of the 19th Century. However, apart from some approaches in broad studies, it has been hardly analized by the literature and journalism reviews. The objective of this article is to delve into some Instructor’s texts related with the Spanish literature and history. Our study try to describe the different perspectives and components that helps in the compose of a national imagery in the papers of the Instructor.